The Design Of Online Cross Country Interactive Dialogue Between Pilipino and Indonesian Pre-Service Teacher in International Research Collaboration - Alfu Nikmah; Rudi Hartono; Issy Yuliasri; Widhiyanto Widhiyanto (International Conference on Science, Education, and Technology, 2023)
Communication is the important factor in conveying the ideas and arguments in cross country research collaboration. Speaking English is a tool communication in the international research collaboration. Therefore it needs a good concept in conducting the research regarding the communication. The purpose of this paper is to describe an online interactive dialogue design for supporting the international research collaboration. Specifically, it examines: (a) how an interactive dialogue design was used to support International Research Collaboration; (b) how activities were structured to promote the level and quality of communications among the students, as peers in the international reseach. The paper also provides information about the delivery process and describes what happened when this interactive model was fully implemented and used